Consideration of Including Male Circumcision in the Indonesian HIV Prevention Strategy - I Nyoman Sutarsa (Public Health and Preventive Medicine Archive, 2014)
The findings from SR on ‘male circumcision for prevention of heterosexual acquisition of HIV in men’ are warranted to be introduced. Male circumcision can reduce HIV transmission among sexually active men by 38 – 66%. This finding is highly relevant to Indonesian context and partially transferable because of: (1) the high prevalence of HIV/AIDS in Indonesia, ranging from concentrated and generalised HIV epidemics; (2) heterosexual contact is a major route of HIV transmission; and (3) the demographic feature of high risk population. These facts alone, however, do not sufficiently address applicability issues to justify implementation. There are three major applicability issues that should be taken into consideration: (1) HIV/AIDS epidemic and the centrality of sex workers in the transmission of HIV in Indonesia; (2) cultural and social reluctance; and (3) health system readiness. Complete community readiness assessment and a complete applicability-transferability attributes assessment are essential prior to adoption. This requirement mandates a new field of research agenda in Indonesia. In the current situation, the SR finding on male circumcision potentially impacts national policy and regulation - particularly in disseminating information strategy. The findings provide immediate justification to start promoting the health benefits of male circumcision to the wider community.